MULTI-DRUG RESISTANT UROPATHOGENS ISOLATED FROM MID STREAM URINE SAMPLES - Regmi, Nisha; Kafle, Sonali; Paudyal, Rabin (Journal of Institute of Science and Technology, 2018)
A frequent and consistent evaluation of the prevalence, etiologic agents and predisposing factors of urinary tract infection (UTI) is necessary in developing country like Nepal to reduce its severe consequences. A regular and routine monitoring of multidrug resistant (MDR) clinical isolates is essential in laboratory practice. Five hundred and ninety one mid stream urine samples were collected from Bharosa Hospital of Kathmandu and a semi-quantitative method was used to determine the frequency of MDR uropathogens in the urine samples. Isolation, identification and antimicrobial susceptibility of isolated bacteria were done by standard microbiological procedure. From the total samples, 161 samples were found to be positive for UTI (27.24 %). Among these bacterial isolates, 57.14 % were found to be MDR. Nitrofurantoin, amikacin and ceftriaxone were found to be the most effective antibiotics against uropathogens.